ANALISIS PERILAKU KONSUMEN GENERASI Z TERHADAP PRODUK SERTIFIKASI HALAL DI PASAR GLOBAL - Arkananta Putra; Nadia Kirana Putri (Yayasan An-Nur Meunara Baro, 2026)
Generation Z currently dominates the global demographic structure and serves as the primary driver for the increasing demand for halal products in the international market. However, their exposure to urban lifestyles and global products often creates ambiguity in consumption priorities. This research aims to identify the factors influencing Generation Z's purchase decisions regarding halal-certified products, focusing on the variables of religiosity, lifestyle trends, and digital information. This study employs a qualitative phenomenological approach with purposive sampling. Data were collected through in-depth interviews, digital observation, and field observation at the Halal Park Integrated Area (Gelora Bung Karno) and modern shopping centers in Central Jakarta, targeting respondents born between 1997 and 2012. The results indicate that digital information and content curation by social media influencers exert a more dominant influence on shaping halal perceptions than formal religious instructions. Although respondents' halal literacy is relatively high, their consumption discipline significantly depends on the extent to which the product intersects with healthy lifestyle trends (clean label) and ethical consumption. The implications of this research emphasize the need for digital marketing strategy adaptation for halal industry developers to better align with the critical and tech-savvy character of Generation Z. This study contributes to the development of a more contextual Sharia economic literacy in facing global market challenges in the age of disruption.